Optimization Of a Smart GPS Tracker System to Measure Truck Speed Performance - Yuniar, Dewi; Yulfadli, Zony; Alnakhli, Mohammad (ZERO: Jurnal Sains, Matematika dan Terapan, 2025)
Smart GPS v 3.3" offers features that traditional systems lack, such as real-time monitoring and advanced travel behavior analysis. This study evaluates the speed of trucks and travel performance using Smart GPS v 3.3 and a tracking system from the stockpile to the port (93.89 km). The methods used were field observation and data collection through smart GPS software. The results show that the trucks average speed/month is 31 km/h for loaded trucks and 57 km/h for empty trucks. The average travel time for loaded trucks is 3:05:36, while for empty trucks it is 2:13:48. In the morning, the travel time for loaded trucks is 2:50:49, and at night it is 3:31:28. The travel time for empty trucks in the morning is 2:50:49 and at night is 2:29:11. The use of GPS serves as an evaluation tool for the coal transport for companies to streamline distribution.